Feasibility of using an artificial intelligence-based telephone application for dietary assessment and nudging to improve the quality of food choices of female adolescents in Vietnam: Evidence from a randomized pilot study - Braga, Bianca C.; Nguyen, Phuong Hong; Tran, Lan Mai; Hoang, Nga Thu; Bannerman, Boateng; Doyle, Frank; Folson, Gloria; Gangupantulu, Rohit; Karachiwalla, Naureen; Kolt, Bastien; McCloskey, Peter; Palloni, Giordano; et al. (Elsevier, 2024)
Background Adolescent nutrition has faced a policy neglect, partly owing to the gaps in dietary intake data for this age group. The Food Recognition Assistance and Nudging Insights (FRANI) is a smartphone application validated for dietary assessment and to influence users toward healthy food choices.